Challenges of scaling up laboratory services for diagnosis and monitoring tests of HIV/AIDS patients on antiretroviral therapy in Zambia - Kahenya, Grace Cecilia (University of Limpopo ( Medunsa Campus ), 2009)
The aim of the study was to determine the challenges of scaling up and strengthening quality-assured laboratory services for diagnosis and monitoring tests for HIV / AIDS patients on Anti- retroviral Therapy (ART). The objectives of the study were to: review the current national HIV/AIDS/STI/TB policy, Laboratory policy, ART strategic plan and guidelines on the implementation of ART services in Zambia; assess the knowledge, attitudes, and practices (KAP) of medical doctors/clinicians and knowledge and practices of laboratory staff in the diagnosis and monitoring tests for HIV / AIDS patients on ART; assess the quality of laboratory services for diagnosis and monitoring tests of HIV / AIDS patients on ART in Zambia compared to WHO standard guidelines; quantify the time taken for CD4 count results to reach the ART centres and determine the difference between the knowledge, attitudes and practices (KAPs) of medical doctors/clinicians in the ART centres with and without laboratory services for diagnosis and monitoring tests for HIV/AIDS patients on ART in Zambia. The study design was a cross-section descriptive survey of one hundred and thirty-seven (137) ART centres in the public health sector of the nine (9) provinces in Zambia. The study population consisted of six directors and managers from the Ministry of Health at national level, medical doctors/clinicians, laboratory staff, district directors of health, in charge of ART centres, and data-entry clerks in charge of Health Information Management Systems (HIMS) from one hundred and thirty-seven (137) ART centres in the public health sector in Zambia. The study findings indicated that only 23% of public sector laboratories were offering a full complement package of quality-assured laboratory services to support the ART programme in Zambia. The HIV/AIDS policy, Laboratory policy, Laboratory Standard Operating Procedures (SOPs) and guidelines on ART scale-up implementation plans exist at national level but had not been fully disseminated to all the ART centres. The average number of qualified laboratory staff at district hospitals surveyed was one (1) qualified laboratory personnel which is lower than the WHO recommendation of four (4) staff per district hospital. Most of the laboratories had no CD4 count machines to support ART V services. Unfortunately, CD4 count results took more than a week to reach the ART centres. Laboratories surveyed indicated a lack of equipment maintenance plans and service contracts. External Quality Assessment for diagnosis and monitoring tests for HIV/AIDS patients on ART was not yet well established. The findings also indicated that Medical Doctors/Clinicians working in the ART centres with laboratory services to support ART programme had better prognosis and treatment of patients on ART compared to those working in the ART centres without laboratory services. There was no difference in the knowledge, attitude and practices of Medical Doctors/Clinicians in the diagnosis and monitoring tests for the management of HIV/AIDS patients on ART in ART centres with and without laboratory service to support the ART programme in Zambia. In conclusion, the Ministry of Health should improve and increase accessibility to fully functional laboratory services to support ART programmes in order to reduce turn-around time for the CD4 count results to reach the ART centres. CD4 count machines should be provided to all the laboratories in ART centres and include service maintenance contracts to support ART services. The policy and decision makers should improve and strengthen the quality of laboratory services by disseminating the National HIV/AIDS policy, Laboratory policy, Laboratory SOPs and guidelines on ART scale-up implementation plan. The recruitment, training and improvement of redistribution of qualified staff should be accelerated to accommodate the current high workload, range of tests performed and an increase in laboratory operations with ART scale-up programme. A standard format of recording and reporting CD4 count results should be put in place (i.e. computerised or manual system). The Ministry of Health should develop guidelines and establish quality assurance systems and affiliate the laboratories to participate in the &ADC regional External Quality Assurance for accreditation such as the South African National Accreditation Systems (SANAS), to support the ART programme.
Thesis (MPH) --University of Limpopo, 2009
Keywords: HIV; AIDS